Automated Good Manufacturing Practice–compliant generation of human monocyte-derived dendritic cells from a complete apheresis product using a hollow-fiber bioreactor system overcomes a major hurdle in the manufacture of dendritic cells for cancer vaccines - Uslu, Ugur; Erdmann, Michael; Wiesinger, Manuel; Schuler, Gerold; Schuler-Thurner, Beatrice (Cytotherapy, 2019)
Background: Although dendritic cell (DC)–based cancer vaccines represent a promising treatment strategy, its exploration in the clinic is hampered due to the need for Good Manufacturing Practice (GMP) facilities and associated trained staff for the generation of large numbers of DCs. The Quantum bioreactor system offered by Terumo BCT represents a hollow-fiber platform integrating GMP-compliant manufacturing steps in a closed system for automated cultivation of cellular products. In the respective established protocols, the hollow fibers are coated with fibronectin and trypsin is used to harvest the final cell product, which in the case of DCs allows processing of only one tenth of an apheresis product. Materials and Results: We successfully developed a new protocol that circumvents the need for fibronectin coating and trypsin digestion, and makes the Quantum bioreactor system now suitable for generating large numbers of mature human monocyte-derived DCs (Mo-DCs) by processing a complete apheresis product at once. To achieve that, it needed a step-by-step optimization of DC-differentiation, e.g., the varying of media exchange rates and cytokine concentration until the total yield (% of input CD14+ monocytes), as well as the phenotype and functionality of mature Mo-DCs, became equivalent to those generated by our established standard production of Mo-DCs in cell culture bags. Conclusions: By using this new protocol for the Food and Drug Administration–approved Quantum system, it is now possible for the first time to process one complete apheresis to automatically generate large numbers of human Mo-DCs, making it much more feasible to exploit the potential of individualized DC-based immunotherapy.
CRIS-Team Scopus Importer:2019-11-12
Keywords: adoptive cell transfer; cell therapy; cellular therapy; dendritic cell vaccine; dendritic cells; immunotherapy; monocyte-derived dendritic cells; vaccines